Polyelectrolyte complexes of DNA and linear PEI: Formation, composition and properties - Perevyazko, Igor Y.; Bauer, Marius; Pavlov, Georges M.; Hoeppener, Stephanie; Schubert, Stephanie; Fischer, Dagmar; Schubert, Ulrich S. (Langmuir, 2012)
In the present study, the complexation between linear 13.4 kDa poly(ethylene imine) (LPEI) and plasmid DNA was investigated. Analytical ultracentrifugation (AUC) was used for size and molar mass determination. Additionally, the morphology was studied by scanning force microscopy. The polyplex formation was investigated in a wide range of PEI nitrogen to DNA phosphate ratios (N/P). At N/P ratios below 1, the PEI/DNA complex formation is characterized by an incomplete DNA condensation and the formation of the primary DNA/PEI complexes. The merging of the initially formed polyplexes occurs at N/P ∼2, resulting in the formation of polyplexes with much larger size and high aggregation rate. Stable and uniform polyplexes were formed at N/P > 10, with average sizes of the polyplexes of about 170 ± 65 nm. The content of uncomplexed PEI chains in the polyplex dispersion was estimated at four different N/P ratios, 6.2, 11.6, 28.6, and 57.8, by combining preparative centrifugation with a copper complex assay and by sedimentation velocity analysis as an alternative method. It is demonstrated that virtually all added PEI binds to the DNA at N/P < 2.5; further addition of PEI results in the appearance of a large amount of free PEI in solution. Nevertheless, PEI is able to bind in the whole range of N/P ratios tested. According to the data collected by sedimentation velocity analysis and scanning force microscopy, the single PEI/DNA complexes are composed on average of 8 to 32 single condensed DNA plasmids and 70 ± 25 PEI molecules. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2020-10-13